2016
DOI: 10.3390/environments3030019
|View full text |Cite
|
Sign up to set email alerts
|

Green Economy Modelling of Ecosystem Services along the “Road to Dawei”

Abstract: This review of the study "Road to Dawei", conducted by WWF Greater Mekong, seeks to assess economic, social and environmental impacts of road construction between Kanchanaburi, Thailand and Dawei, Myanmar. It also aims to identify relevant Green Economy policy interventions that would enhance the sustainable use and conservation of natural capital, which is considered to be a foundation for sustainable and inclusive economic development. In particular, the study concentrates on the identification of feedback l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Walsh, ) by encouraging development, shortening transportation times of major goods, and becoming a new gateway to Southeast Asia. While Environmental Impact Assessments are not legally required in Myanmar (Kattelus et al ., ), developments are projected to have substantial implications for biodiversity and ecosystem services (Bassi et al, ). As well as direct loss during construction, increasing transport links (roads, ports) are associated with longer term habitat declines as new development gateways are opened (Laurance et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Walsh, ) by encouraging development, shortening transportation times of major goods, and becoming a new gateway to Southeast Asia. While Environmental Impact Assessments are not legally required in Myanmar (Kattelus et al ., ), developments are projected to have substantial implications for biodiversity and ecosystem services (Bassi et al, ). As well as direct loss during construction, increasing transport links (roads, ports) are associated with longer term habitat declines as new development gateways are opened (Laurance et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Attempts are being made to come to ceasefire agreements with rebel groups (Myanmar Times, 2012), and several large scale economic development projects are planned, such as the Dawei Special Economic Zone, that may fundamentally shift regional trade dynamics by opening new trade routes between Europe/the Middle East and Asia (Findlay et al, 2016). These projects are expected to have substantial detrimental impacts on the environment by encouraging agricultural and urban development (Bassi et al, 2016). The palm oil industry is an emerging threat to mangrove forests in the region (Richards & Friess, 2016), and is a threat that is expanding in Tanintharyi due to suitable soil and climatic conditions that are not found elsewhere in the country (FFI, 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…It has a tropical climate with significant rainfall most months and a short dry season. The area includes the Tenasserim Hills, where the Myinmoletkat Taung is the highest point with 2072 m. The area harbours one of the last large intact forest landscapes in the region, which hosts a large number of ethnic groups, and a wide variety of endangered wildlife such as elephants and tigers [33]. The region is experiencing numerous threats including rapid increase in agricultural land use and associated deforestation, notably for rubber and palm oil, road and infrastructure development, and logging resulting in habitat degradation and fragmentation [34].…”
Section: Study Regionmentioning
confidence: 99%
“…Also, full development of the Dawei Special Economic Zone, although stalled since 2008, could catalyse further infrastructure development in the region, particularly along the forested Thailand-Myanmar border, and thus lead to further deforestation. A simulation study, for example, along the "Road to Dawei" demonstrated this possibility wherein a conventional approach to road construction was likely to have positive economic impacts in the region, especially in the short-term, but also negative consequences for the integrity of the ecosystem, which in turn might also negatively impact the investment itself and its economic outcomes in the medium and longer term [88].…”
Section: Historical and Possible Future Drivers Of Land-cover Regime mentioning
confidence: 99%